2008
DOI: 10.1002/hyp.7022
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall‐discharge relationships for a monsoonal climate in the Ethiopian highlands

Abstract: This study presents a simple rainfall-discharge analysis for the Andit Tid, Anjeni, and Maybar watersheds of northern Ethiopia. The Soil Conservation Research Programme (SCRP) established monitoring stations in each of these sites during the 1980s, with climate and stream flow measurements being recorded up to the present. To show how these data could be used to provide insight into catchmentlevel runoff mechanisms, simple linear relationships between effective precipitation and runoff are developed for each w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 16 publications
7
127
0
Order By: Relevance
“…Precipitation, discharge and storm event sediment yields are available from 1988-1994, 1996-2004, and 2008 (Table 1). 16901984-1993-2013Liu et al, 2008Guzman et al, 2013;Tilahun et al, 2013a,b;Elkamil, 2014;Tebebu et al, 2014;Bayabil et al, 2015 Maybar 113 Phaeozems and Phaeozems associated to Lithosols 12101988-19941996-2004Liu et al, 2008Bayabil, 2009;Bayabil et al, 2010;Guzman et al, 2013 Andit Tid 481 Andosols and Regosols 15001986-19921994-2001Liu et al, 2008Engda, 2009;Guzman et al, 2013;Tilahun et al, 2013b Debre Mewi 95 Nitosols and Vertisols 1240-2014Abiy, 2009Tebebu, 2009;Tebebu et al, 2010;Zegeye et al, 2010;Tilahun, 2012;Langendoen et al, 2013;Dagnew et al, 2014;Tebebu et al, 2014;Zegeye et al, 2014;Dagnew et al, 2015;Tilahun et al, 2015 The Andit Tid watershed, situated 180 km northeast of Addis Ababa at 39 • 43 ′ E and 9 • 48 ′ N, covers 481 ha ( …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Precipitation, discharge and storm event sediment yields are available from 1988-1994, 1996-2004, and 2008 (Table 1). 16901984-1993-2013Liu et al, 2008Guzman et al, 2013;Tilahun et al, 2013a,b;Elkamil, 2014;Tebebu et al, 2014;Bayabil et al, 2015 Maybar 113 Phaeozems and Phaeozems associated to Lithosols 12101988-19941996-2004Liu et al, 2008Bayabil, 2009;Bayabil et al, 2010;Guzman et al, 2013 Andit Tid 481 Andosols and Regosols 15001986-19921994-2001Liu et al, 2008Engda, 2009;Guzman et al, 2013;Tilahun et al, 2013b Debre Mewi 95 Nitosols and Vertisols 1240-2014Abiy, 2009Tebebu, 2009;Tebebu et al, 2010;Zegeye et al, 2010;Tilahun, 2012;Langendoen et al, 2013;Dagnew et al, 2014;Tebebu et al, 2014;Zegeye et al, 2014;Dagnew et al, 2015;Tilahun et al, 2015 The Andit Tid watershed, situated 180 km northeast of Addis Ababa at 39 • 43 ′ E and 9 • 48 ′ N, covers 481 ha ( …”
Section: Methodsmentioning
confidence: 99%
“…The hydrological similarity over 14 day periods in watersheds can be seen by comparing the long-term discharge and sediment concentrations of the three SCRP watersheds (Figures 2, 3, 4), namely Andit Tid, Anjeni, and Maybar, located hundreds of kilometers apart. Liu et al (2008) showed that for cumulative seasonal effective rainfall of 500 mm or more the proportion of rainfall that becomes runoff is remarkably the same. Figure 2 which is redrawn from Liu et al (2008) shows that for all three watersheds, the discharge over a 14 day period as a function of the effective rainfall (defined as precipitation minus potential evaporation).…”
Section: Hydrological Similarity Of Watershedsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SWAT model is based on the Soil Conservation Service (SCS) runoff curve number approach, where the parameter values are obtained empirically from plot data in the United States with a temperate climate. Liu et al (2008) studied the rainfall-runoff relationships for the three Soil Conservation Research Project (SCRP) watersheds (Hurni, 1984) in the Ethiopian highlands and showed the limitations of using such models, developed in temperate climates, in monsoonal Ethiopia. Adjusted runoff curve numbers for steep slopes with natural vegetation in northern Ethiopia were reported by Descheemaeker et al (2008).…”
Section: Introductionmentioning
confidence: 99%